البُنى التحتية لمحطاتِ الرصد الجوي في محافظةِ واسط - والي فريح الركابي, ناصر; رزاق عبود, صدام (Journal of College of Education, 2019)
Waiting of Air-monitoring station working in the Wasit district is clearly affected bynatural changes of climate change in elements and opinions climatic, Which contributed directly and indirectly in the low efficiency of field of air station. Risk elements climatic such as solar radiation, temperatures and winds as well as increased Dust Phenomena in the deterioration of infrastructure for  aircraft stations. This was accompanied by natural change in human factors it has increased the area of cities with air terminals, so that these stations are within the basic design of cities, It has not taken of the precision of the optimal location of the station and has been reflected on the nature of those of the air strikes. Government neglect and the insistence of those air strikes were an additional factor in the development of infrastructure problems of aircraft stations.